Fatigue and perceived social support contributing to medication adherence among elderly patients with musculoskeletal disorders in Greece - Paraskevi Theofilou; Eleni Anyfantopoulou (Academia Medicine)
The aim of the present study was to explore the contribution of fatigue and perceived social support to medication adherence among elderly patients with musculoskeletal disorders in Greece. In this study, 145 elderly patients (51 males and 94 females) with musculoskeletal disorders participated. It was a convenience sample, which means that participants were selected based on their accessibility and availability to the researcher. The mean age was 74.8 ± 9.12 years. The Fatigue Assessment Scale (FAS), the Self-Efficacy for Appropriate Medication Use Scale (SEAMS), and the Multidimensional Scale of Perceived Social Support (MSPSS) were used to collect research data. Physical fatigue was significantly and negatively correlated to medication adherence (p < 0.05). Furthermore, mental fatigue was significantly and negatively correlated to medication adherence, social support gained from significant others and family, and total social support (p < 0.05). Total fatigue was also significantly and negatively correlated with medication adherence, social support gained from significant others and family, and total social support (p < 0.05). Additionally, social support from family was significantly and negatively correlated with medication adherence (p < 0.05). The findings show a strong association of medication adherence with social support and fatigue.